Explainable Deep Learning Model Using Class Activation Maps in Lung Cancer Testing and Radiologist Evaluation - Tunçer, Savaş; Katar, Oğuzhan; Öztürk, Tülin; Yıldırım, Özal (Ankara Bilim University, 2024)
Lung cancer is one of the most common and deadly cancer types worldwide. Early diagnosis of lung cancer allows detecting the disease at a treatable stage, which significantly increases the patient's chances of survival. The use of artificial intelligence in this field can help detect the disease more effectively, providing a number of advantages. Recently, deep learning approaches have taken a dominant role in image classification studies. One of the most important disadvantages of deep learning methods is the lack of transparency in terms of reliability due to their closed-box structure. For this purpose, explainable models have become an important research area. Explainable deep learning models are generally based on techniques such as class activation maps (CAM). In this study, an explainable deep learning model was created for lung cancer detection. The experimental studies within the scope of the article were conducted on an open-access dataset containing lung computed tomography (CT) images. In the classification phase, convolutional neural networks (CNN) based ResNet101V2, VGG16, MobileNetV2, DenseNet201 and EfficientNetB0 models were used. According to experimental results, the EfficientNetB0 model reached the highest classification accuracy of 98.63%. Heat maps were obtained with different CAM techniques applied to the classifier model. The resulting heat maps were evaluated by the expert radiologist and the results were discussed.

Akciğer kanseri dünya genelinde yaygın ve ölümcül olan kanser türlerinden biridir. Akciğer kanserinin erken tanısı, hastalığın tedavi edilebilir aşamada tespit edilmesine olanak tanır ve bu da hastanın yaşam şansını önemli ölçüde artırır. Yapay zekânın bu alanda kullanımı, bir dizi avantaj sağlayarak hastalığın daha etkili bir şekilde tespitine yardımcı olabilir. Son zamanlarda derin öğrenme yaklaşımları görüntü sınıflandırma çalışmalarında baskın bir rol almaktadır. Derin öğrenme yöntemlerinin en önemli dezavantajlarından birisi kapalı-kutu yapısı nedeniyle güvenirlik açısından şeffaflık eksikliğidir. Bu amaçla açıklanabilir modeller önemli bir araştırma haline gelmiştir. Açıklanabilir derin öğrenme modelleri, genellikle sınıf aktivasyon haritaları (Class Activation Maps - CAM) gibi tekniklere dayanmaktadır. Bu çalışmada, akciğer kanseri tespitinde açıklanabilir bir derin öğrenme modeli oluşturulmuştur. Makale kapsamındaki deneysel çalışmalar, akciğer bilgisayarlı tomografi (BT) görüntülerini içeren ve açık erişimli bir veri seti üzerinde yürütülmüştür. Sınıflandırma aşamasında konvolüsyonel sinir ağları (KSA) tabanlı ResNet101V2, VGG16, MobileNetV2, DenseNet201 ve EfficientNetB0 modelleri kullanılmıştır. Deneysel sonuçlara göre EfficientNetB0 modeli %98.63 ile en yüksek sınıflandırma doğruluğuna ulaşmıştır. Sınıflandırıcı modele uygulanan farklı CAM teknikleri ile ısı haritaları elde edilmiştir. Elde edilen ısı haritaları uzman radyolog tarafından değerlendirilerek sonuçlar tartışılmıştır.
Akciğer Kanseri Tespitinde Sınıf Aktivasyon Haritaları Kullanarak Açıklanabilir Derin Öğrenme Modeli ve Radyolog Değerlendirmesi
Keywords: Software Engineering (Other); Yazılım Mühendisliği (Diğer)